Re-telling the story of aminoglycoside ototoxicity: tales from sub-Saharan Africa - Adeyemo, Adebolajo A.; Adedokun, Babatunde; Adeolu, Josephine; Akinyemi, Joshua O.; Omotade, Olayemi O.; Oluwatosin, Odunayo M. (Frontiers in Neurology, 2024)
Background: Aminoglycosides, such as Streptomycin, are cheap, potent antibiotics widely used Sub-Saharan Africa. However, aminoglycosides are the commonest cause of ototoxicity. The limited prospective epidemiological studies on aminoglycoside ototoxicity from Sub-Saharan Africa motivated this study to provide epidemiological information on Streptomycin-induced ototoxicity, identify risk factors and predictors of ototoxicity.Method: A longitudinal study of 153 adults receiving Streptomycin-based anti-tuberculous drugs was done. All participants underwent extended frequency audiometry and had normal hearing thresholds at baseline. Hearing thresholds were assessed weekly for two months, then monthly for the subsequent six months. Ototoxicity was determined using the ASHA criteria. Descriptive statistics were used to analyze socio-demographic variables. Ototoxicity incidence rate was calculated, and Kaplan-Meier estimate used to determine cumulative probability of ototoxicity.Chi-square test was done to determine parameters associated with ototoxicity and Cox regression models were used to choose the predictors of ototoxicity.Results: Age of participants was 41.43±12.66 years, with a male-to-female ratio of 1:0.6. Ototoxicity was found in 34.6% of the participants, giving an incidence of 17.26 per 1000person-week. The mean onset time to ototoxicity was 28.0±0.47 weeks. By 28th week, risk of developing ototoxicity for respondents below 40 years of age was 0.29, and for those above 40 years was 0.77. At the end of the follow-up period, the overall probability of developing ototoxicity in the study population was 0.74. A significant difference in onset of ototoxicity was found between the age groups: the longest onset was seen in <40 years, followed by 40-49 years, and shortest onset in ≥50 years. Hazard of ototoxicity was significantly higher in participants aged ≥50 years compared to participants aged ≤40 years (HR = 3.76, 95% CI = 1.84 -7.65). The probability of ototoxicity at 40g, 60g and 80g cumulative dose of Streptomycin was 0.08, 0.43 and 2.34, respectively. Age and cumulative dose were significant predictors of ototoxicity.The mean onset time to Streptomycin-induced ototoxicity was twenty-eight weeks after commencement of therapy. Age and cumulative dose can reliably predict the onset of Streptomycin-induced ototoxicity. Medium to long term monitoring of hearing is advised for patients on aminoglycoside therapy.